Preclinical assessment of adjunctive tPA and DNase for peritoneal dialysis associated peritonitis - McGuire, A.; Bennett, S.; Lansley, S.; Popowicz, N.; Della Vergiliana, J.; Wong, D.; Lee, Y.; Chakera, Aron (Public Library of Science, 2015)
Copyright: #x000a9; 2015 McGuire et al. A major complication of peritoneal dialysis is the development of peritonitis, which is associated with reduced technique and patient survival. The inflammatory response elicited by infection results in a fibrin and debris-rich environment within the peritoneal cavity, which may reduce the effectiveness of antimicrobial agents and predispose to recurrence or relapse of infection. Strategies to enhance responses to antimicrobial agents therefore have the potential to improve patient outcomes. This study presents pre-clinical data describing the compatibility of tPA and DNase in combination with antimicrobial agents used for the treatment of PD peritonitis. tPA and DNase were stable in standard dialysate solution and in the presence of antimicrobial agents, and were safe when given intraperitoneally in a mouse model with no evidence of local or systemic toxicity. Adjunctive tPA and DNase may have a role in the management of patients presenting with PD peritonitis.